Angle Class I malocclusion with anterior open bite treated with extraction of permanent teeth - Matheus Melo Pithon (Dental Press Journal of Orthodontics, 2013)
This clinical case reports the orthodontic treatment of a Class I malocclusion with anterior open bite and bimaxillary dentoalveolar protrusion in a 28-year-old female patient. The treatment of choice was to perform tooth extractions followed by retraction of the anterior teeth, with consequent closure of the anterior open bite and better accommodation of the teeth on their bony bases. This case was presented to the Brazilian Board of Orthodontics and Facial Orthopedics (BBO), representing the Category 2 - i.e., an Angle Class I malocclusion, with anterior open bite, treated with extraction of permanent teeth -, as part of the requisites to become a BBO diplomate.